Analisis Pengaruh Kualitas Produk, Persaingan Harga dan Kualitas Layanan Aplikasi terhadap Kepuasan Pengguna Layanan Aplikasi Online Shop di Kota Medan - Elvina Barutu; Fedita Debyani Siahaan; Kalara Sukmawati br Simanjuntak (ISLAMIKA, 2022)
The purpose of this study is to test and analyze the effect of product quality, price competition and application service quality on user satisfaction of online shop application services in Medan City, the method in this study uses a quantitative approach and the nature of the research uses descriptive methods, the population in this study is customers. on the online shop application users in the Medan Tembung area as many as 139,249 people, the sampling technique used the slovin formula with a % error of 10% obtained 100 respondents used in this study, based on the results of SPSS data processing, the partial hypothesis results for the value of product quality have a tcount value of 4.513 > ttable 1.66105, price competition has a tcount value of 2.600 > ttable 1.66105 while the quality of application services has a tcount value of 3.272 > ttable 1.66105 which means product quality, price competition and application service quality have a positive and significant effect on user satisfaction of online shop application services in Medan City, while simultaneously the fcount value is (81.951) > ftable is (2.14) with a significant value of 0.000 < 0.10 which means product quality, price competition and application service quality have a positive and significant effect on user satisfaction of online shop application services in Medan City.